Tidal bending of ice shelves as a mechanism for large-scale temporal variations in ice flow - Rosier, Sebastian; Gudmundsson, Hilmar (The Cryosphere, 2018)
GPS measurements reveal strong modulation of horizontal ice shelf and ice stream flow at a variety of tidal frequencies, most notably a fortnightly (Msf) frequency not present in the vertical tides themselves. Current theories largely fail to explain the strength and prevalence of this signal over floating ice shelves. We show how well-known non-linear aspects of ice rheology can give rise to widespread, long-periodic tidal modulation in ice shelf flow, generated within ice shelves themselves through tidal flexure acting at diurnal and semidiurnal frequencies. Using full-Stokes viscoelastic modelling, we show that inclusion of tidal bending within the model accounts for much of the observed tidal modulation of ice shelf flow. Furthermore, our model shows that, in the absence of vertical tidal forcing, the mean flow of the ice shelf is reduced by almost 30 % for the geometry that we consider.